Corporate Debt Structure and the Financial Crisis - Fiorella De Fiore; Harald Uhlig (European Central Bank (ECB), 2015)
We present a DSGE model where firms optimally choose among alternative instruments of external finance. The model is used to explain the evolving composition of corporate debt during the financial crisis of 2008-09, namely the observed shift from bank finance to bond finance, at a time when the cost of market debt rose above the cost of bank loans. We show that the flexibility offered by banks on the terms of their loans and firms' ability to substitute among alternative instruments of debt finance are important to shield the economy from adverse real effects of a financial crisis.
Keywords: E32; E44; C68; G23; 330; corporate debt; financial crisis; firms heterogeneity; risk shocks; Unternehmensfinanzierung; Fremdkapital; Kredit; Unternehmensanleihe; Finanzkrise; Bankenkrise; DSGE-Modell; Theorie; Welt